Influences of initial coal concentration on ignition behaviors of low-NOx bias combustion technology. (15th November 2020) - Zeng, Guang; Xu, Mingchen; Tu, Yaojie; Li, Zhenwei; Cai, Yongtie; Zheng, Zhimin; Tay, Kunlin; Yang, Wenming
Highlights: A 250-kW bias combustion facility with an optical method was employed. The ignition behaviors improved gradually with increasing initial coal concentration. A transition of ignition mechanism occurred as initial coal concentration increased. After engineering application, the boiler NOx emission decreased by 29 mg/Nm 3 . The highest initial coal concentration of horizontal bias combustion can increase to 0.53 kg/kg. Abstract: In order to provide the key parameters of initial coal concentration to low-NOx bias combustion technology and enrich the pulverized-coal bias combustion theory, pilot-scale ignition experiments of bias coal streams were carried out using a 250-kW fuel input bias combustion facility. The experimental results including combustion temperature, unburned residues, gas species, and flame spectra were collected. The influences of initial coal concentration on the ignition behaviors of an Indonesian subbituminous in a reducing atmosphere were studied. Our findings show that as initial coal concentration increased, the intensity of visible light and the carbon burnout progressively increased, while the ignition distance and the fuel NOx formation continually decreased. It was observed that the region of continuous flame became successively concentrated, and the flame stability was increasingly enhanced, indicating that the ignition behaviors improved in a gradual way. Furthermore, the mechanism of the combined homo-heterogeneous ignition changed to homogeneous ignition. To be specific, at initial coal concentrations of 0.33 kg/kg and 0.41 kg/kg, the homo-heterogeneous combined ignition mechanism occurred. While at an initial coal concentration of 0.53 kg/kg, the mechanism changed to homogenous ignition. For a tangentially-fired pulverized-coal boiler burning the Indonesian subbituminous, the highest initial coal concentration of the horizontal bias combustion burners can be designed as 0.53 kg/kg, which will be beneficial to the strong ignition and low-NO x emission.